CULTURAL TOOLS TO ENHANCE LEARNING - Natalie Senjov-Makohon (European Scientific Journal, ESJ, 2014)
The cultural tools to connect, communicate, and prepare learners for future academic and workplace activities underpin today’s education. In the 21st century, the use of technologies, and in particular social technologies, provide a paradigm shift in the way teachers become engaged and personalize professional development. The technologies are the cultural tools (Vygotsky, 1975, p. 3) deployed to communicate and analyze learners’ realities; however, some experienced teachers are reluctant to embrace these realities. However, there are other teachers who are adopting the 21st century cultural tools to make their learning and the learning of their students relevant, social and personal. This paper examines how social practices and cultural tools deployed, in a study with experienced teachers, adds value to teacher professional development. It examines the scaffolding with social technologies to enable learners to progress to higher order development in a Zone of Proximal Development (Vygotsky, 1978) in Higher Education.